The Moonlighting Intention in Indonesian Public Community College Employee: A Perceived Threat Moderated Mediation Model - Pujianto, Hendri; Sarsono; Pawenang, Supawi; Sudarwati (UIN Raden Mas Said Surakarta, 2024)
This study headed to probe the moonlighting intentions (MI) empirically from non-monetary factors, including job satisfaction (JS) through the mediation of organizational commitment (OC) and the moderation role of perceived COVID-19 threats (PCT) and perceived financial threats (PFT) during the pandemic. The study accustomed quantitative methods with a survey and a cross-sectional design. This study gathered data from 81 employees at Community College (AK-Tekstil Solo) and analyzed it using SMART PLS. This study discovered that job satisfaction majorly impacts organizational commitment and moonlighting intentions. Organizational commitment negatively influences moonlighting intentions due to its indirect-only (full mediation) relationships with job satisfaction. PCT and PFT did not play a moderating role, but they did diminish the effect sizes between constructs. The results of this study confirmed the substantial non-monetary facets of moonlighting intentions. This research contributes to the development of theory by validating the relationships that it draws from social exchange theory, and the novelty is the introduction of moderating variables in terms of threat aspects perceived during the pandemic, PCT, and PFT. The relevance of the research findings provides some practical implications and valuable insights for managers of formal educational institutions in the environmental condition that may change at any time without certainty